Media linguistics in South Asia : language, culture and communication - Fatihi, A. R. (New York, NY : Routledge, 2023)
"The tone and texture of the language of media have changed considerably due to the rapid expansion of media in recent times and advancements in communication technologies. This book examines new ways to conduct linguistic explorations into the myriad of forms news is being presented and consumed. It contributes to the emerging field of media linguistics by measuring and analysing the associations between linguistics and the news discourse. It extends the conceptualization of language-media relations in sociolinguistics beyond the notions of 'influence' and 'effect' and broadens the theoretical and empirical scope of the discipline. The book discusses different perspectives of media linguistics; issues of variation in language of media; question of plurilingual resources; parallel language use in media and textuality of news genres. It discusses the dynamics of news reportage by studying the coverage of conflicts, violence and dissent in South Asian media in recent decades along with the reportage of cricket headlines and news. Comprehensive and topical this volume will be useful for scholars and researchers of linguistics, media linguistics, applied linguistics, media studies, media sociology, sociology, cultural studies and South Asian studies"--
Includes bibliographical references and index.
Keywords: Mass media and language -- South Asia; Discourse analysis -- South Asia; Sociolinguistics -- South Asia